Sistemas lineares na segunda série do ensino médio: um olhar sobre os livros didáticos - Battaglioli, Carla dos Santos Moreno (2008)
This task has as a goal to make a qualitative analysis about the linear system aprouch presented in three didatic books of the high school program that were aproved by the Programa Nacional do Livro Didático para o Ensino Médio (PNLEM). The research is based in the theorical reference of the Registers of the Semiotics Representation by Raymond Duval (2003), because we believe in the importancy of the register s conversion in order to build the student s knowledge. Our proposal is to check in these didatic books in which registers of the semiotics representation the linear systems are presented and which register s conversion are proposed in their exercises. We chose to analyse didatic books because we believe they are the instruments used the most by the teachers to prepare and to give classes. This way, the didatic books can determine the content and strategies to be worked in class. This research lead us also to investigate which are the orientations in some oficial documents: Complementary Educacional Orientations to the Nacionals Curriculares Parameters (PCN+) (BRASIL, 2002); Curriculares Orientations to High school teachers (BRASIL, 2006) and the PNLEM recomendations (BRASIL, 2007). From these documents we will do a comparision between the method of the stagger in the graphical and algebraical registers. The results obtained show that the graphical register and the register of semiotic representation of the natural language are pesented in two of the three books anlysed, however the graphic register is presented only in explanation texts, beeing few explored in the solved exercises or in the proposed exercises. We also observedthat the algebraical register is still prevailling in the linear system aprouch and that the algorithm to the resolution of systems has still beeing treated in first view, while the analyse of the results obteined in the resolution or classification of a linear system is still explored timidly